Menggali Potensi Kreativitas Anak Melalui Ecoprint - Anggun Marfuah; Sulistyani Putri Kinanti; Putri Handayani; Naily Hani’ah; Defta Nasya Berliani; Dian Rif'iyati (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
One of the work programs of KKN students batch 56 batch 20 UIN KH. Abdurrahman Wahid Pekalongan is an ecoprint. The target of this activity is elementary school children and their age. This study aims to determine the application of children's creativity by utilizing natural potential through ecoprint activities and learning reflection tools that can create environmentally friendly products. The method used in this research is planting, socialization, and direct practice. This research took place in a collaborative manner which was attended by elementary school children and led by the KKN 56 Team of 20 UIN KH. Abdurrahman Wahid Pekalongan. Observations in this study were carried out directly by observing elementary school children's activities in the coloring process using ecoprinting techniques and observing how ecoprinting activities can stimulate children's skills and creativity. Data collection is done by observation and documentation. The results of the study show that coloring activities using the ecoprint technique are learning innovations for children by utilizing natural potential to explore skills and creativity in children. In addition, natural materials that are around children can be an inspiration for children to learn how to create new products that are environmentally friendly.